A generalized thermal deviation factor to evaluate the comprehensive stress of tubes under non-uniform heating. (15th January 2023) - Li, X.L.; Li, G.X.; Tang, G.H.; Fan, Y.H.; Yang, D.L.
Abstract: The heaters working with supercritical fluids normally suffer from high temperature, high pressure and non-uniform heating, which would lead to thermal fragile and stress failure in practical engineering. However, efficient and accurate methods to predict the comprehensive stress in non-uniformly heating tubes are missing. Besides, to reduce the comprehensive stress, a criterion is required to provide optimization guidance of non-uniformly heating tubes. In present study, the thermal and mechanical performances of three typical non-uniformly heating tubes are numerically investigated using the FVM-FEM method. A generalized thermal deviation factor ( GTDF ) is then proposed. The results showed that the GTDF can accurately predict the ratio of comprehensive stress to yield strength and GTDF > 1 indicates the plastic deformation, which is much more convenient and efficient than the conventional structural analysis. Based on the GTDF, two methods of reducing heat flux non-uniformity and enhancing tube-inside heat transfer are proposed to reduce the comprehensive stress. The results show that the unilaterally elliptic dimpled tube reduces the maximum comprehensive stress by 30.8% compared with the smooth tube and also prevents the stress concentration in the dimple zone, which can be employed to reduce the comprehensive stress in various tubes under non-uniformly heating conditions. Highlights: Thermal and comprehensive stresses in non-uniformly heating tubes were discussed. A new criterion called GTDF was proposed to evaluate comprehensive stress. The GTDF is more efficient and intuitive than the comprehensive stress. Two methods are proposed to reduce the comprehensive stress based on the GTDF. The elliptic dimple is recommended in non-uniformly heating tubes.